Tafsir Al-Qur’an Surah Ibrahim Ayat 4 dan Relevansinya dengan Media Dakwah Digital: Tafsir Al-Qur'an Surah Ibrahim Verse 4 and Its Relevance to Digital Dakwah Media - Nahdiyah, Naila (STAI Ma'had Aly Al-Hikam Malang, 2025)
This study discusses the relevance of QS. Ibrahim verse 4 to the practice of da'wah in the digital era through the tafsir al-tsaqafī approach. The verse emphasizes the principle of bi lisāni qoumihi—that every delivery of da'wah messages must be adapted to the language, culture, and social context of the recipient community. Language is a medium of da'wah, and in this digital era, da'wah media has developed rapidly and da'is have used social media in their da'wah practices. Therefore, it is necessary to study the text of the Qur'an that explains the basis of da'wah media. This study uses a library research method by examining QS. Ibrahim verse 4 in the tafsir of Ibn Kathir and Al-Misbah, to examine the relationship between the text of revelation and the reality of digital da'wah. The results of the study show that digital da'wah is a logical continuation of conventional da'wah which demands the adaptive ability of da'is in using social media as a communicative and ethical da'wah medium. QS. Verse 4 of Ibrahim not only emphasizes the importance of language in conveying religious messages, but also fosters critical awareness that knowledge and da'wah must be grounded in divine values, communication ethics, and an understanding of digital culture. Thus, this verse serves as a conceptual foundation for the development of da'wah and a culture of knowledge that is humanistic, reflective, and relevant to the challenges of the modern era